2013
DOI: 10.1016/j.nicl.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal T2 hyperintensities on 7Tesla MRI

Abstract: Hippocampal focal T2 hyperintensities (HT2Hs), also referred to as hippocampal sulcal cavities, are a common finding on Magnetic Resonance (MR) images. There is uncertainty about their etiology and clinical significance. In this study we aimed to describe these HT2Hs in more detail using high resolution 7 Tesla MR imaging, addressing 1) the MR signal characteristics of HT2Hs, 2) their occurrence frequency, 3) their location within the hippocampus, and 4) their relation with age. We also performed an explorativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Due to their small size, in many cases microinfarcts are not detected with standard imaging tools; therefore regional abnormalities in brain structures are assumed to reflect sites of damage, while actual affected networks may be more widely distributed. Nonetheless, there is evidence that regions such as the hippocampus and white matter tracts may accumulate more hyperintense damaged regions compared to the rest of the brain (van Veluw et al, 2013). Animal models of microinfarction can be used to systematically identify sites of damage and also reflect the trend for a greater number of infarcts in vulnerable brain regions (Wang et al, 2012).…”
Section: Interhemispheric Balance Is Altered After Stroke and Can Bmentioning
confidence: 99%
“…Due to their small size, in many cases microinfarcts are not detected with standard imaging tools; therefore regional abnormalities in brain structures are assumed to reflect sites of damage, while actual affected networks may be more widely distributed. Nonetheless, there is evidence that regions such as the hippocampus and white matter tracts may accumulate more hyperintense damaged regions compared to the rest of the brain (van Veluw et al, 2013). Animal models of microinfarction can be used to systematically identify sites of damage and also reflect the trend for a greater number of infarcts in vulnerable brain regions (Wang et al, 2012).…”
Section: Interhemispheric Balance Is Altered After Stroke and Can Bmentioning
confidence: 99%
“…For ONDRI, the SBHV segmentation has been fully integrated into the SABRE-LE pipeline, and includes left and right hippocampal sub-classifications for parenchyma, hypointensities, and stroke volumes (when present). Currently, there is some controversy over the pathophysiological origin and relevance of small cavities commonly observed in the hippocampus (Bastos- Leite et al, 2006;Maller et al, 2011;Van Veluw et al, 2013;Yao et al, 2014), which are particularly relevant in the ONDRI VAS patients. Additionally, large cortico-subcortical strokes can extend from the cortex into the hippocampus.…”
Section: Hippocampusmentioning
confidence: 99%
“…According to others, HSCs are dilated perivascular spaces (dPVS), also known as dilated Virchow-Robin spaces (dVRS) (Kwee and Kwee 2007). Previous studies found a higher number of HSCs with an increasing mean arterial pressure (MAP) (Van Veluw et al 2013), and with higher systolic and diastolic blood pressure (Yao et al 2014), suggesting that the etiology of HSCs may be related to vascular factors . However, a review reported that the relation between HSCs and hypertension has been questioned and that some studies excluded patients with hypertension (Maller et al 2011).…”
Section: Introductionmentioning
confidence: 99%